THE EFFECTIVENESS OF GREEN BUDGETING IN SUPPORTING SUSTAINABLE FINANCIAL PRACTICES IN PUBLIC COMPANIES - Yusran Zainuddin; Nova Yanti Maleha; Muhammad Naihul Author (Adisam Publisher, 2025)
This research aims to analyze the effectiveness of green budgeting in supporting sustainable financial practices in public companies thru a systematic literature review (SLR) approach. Green budgeting is defined as a budgeting process that integrates environmental goals into the company's resource allocation to achieve a balance between profitability, social responsibility, and environmental sustainability in accordance with the principles of Environmental, Social, and Governance (ESG). Data was collected from reputable academic literature, official OECD reports, corporate sustainability documents, and relevant government regulations. Content analysis is used to identify key themes, including the concepts and application of green budgeting, its contribution to sustainable finance, and its supporting and hindering factors. The study results indicate that green budgeting is effective in increasing resource efficiency, reducing carbon footprint, supporting the achievement of Sustainable Development Goals (SDGs), strengthening reputation, and enhancing investor confidence. The main supporting factors include top management commitment, regulatory support, advancements in reporting technology, and stakeholder participation. However, its implementation still faces challenges such as high initial costs, limited environmental data, internal resistance, and a lack of fiscal incentives. This study recommends integrating green budgeting into long-term business strategies, strengthening environmental data systems, and cross-sector collaboration to expand its positive impact. This finding is expected to serve as a reference for public companies and policymakers in promoting green budgeting as a pillar of sustainable finance in the ESG era.